Inhomogeneous Dirichlet-boundary value problem for nonlinear Schrödinger equations with a power nonlinearity on the upper half-plane. (October 2019) - Hayashi, Nakao; Kaikina, Elena I.
Abstract: We consider the inhomogeneous Dirichlet-boundary value problem for nonlinear Schrödinger equations with a power nonlinearity in the upper half plane. We present sufficient conditions of initial and boundary data which ensure asymptotic behavior of small solutions to the problem by using the classical energy method and factorization techniques.